Obesity Challenge Drives Distinct Maternal Immune Response Changes in Normal Pregnant and Abortion-Prone Mouse Models - Li, Yanhong; Chen, Jiajia; Lin, Yikong; Xu, Ling; Sang, Yifei; Li, Dajin; Du, Meirong (Frontiers in Immunology, 2021)
Obesity is prevalent among women of reproductive age and is associated with increased risk of developing multiple pregnancy disorders. Pregnancy must induce immune tolerance to avoid fetal rejection while obesity can cause chronic inflammation through activating the immune system. Impaired maternal immuno-tolerance leads to pregnancy failure, such as recurrent spontaneous abortion (RSA), one of the most common complications during early pregnancy. How does maternal immune response change under obesity stress in normal pregnancy and RSA? In turn, is obesity affected by different gestational status? Limited information is presently available now. Our study investigated pregnancy outcomes and maternal immune responses in two murine models (normal pregnancy and spontaneous abortion models) after obesity challenge with a high-fat diet (HFD). Abortion-prone mice fed HFD had significantly higher weight gains during pregnancy than normal pregnant mice with HFD feeding. Nonetheless, the embryo implantation and resorption rates were comparable between HFD and normal chow diet (NCD)-fed mice in each model. Evaluation of immune cell subsets showed HFD-induced obesity drove the upregulation of activated NK cell-activating receptor (NKp46)+ NK cells and proinflammatory macrophages (MHCIIhigh Mφ) as well as CD4+ and CD8+T cells in the normal pregnancy group. However, in the abortion-prone group, relative more immature NK cells with decreased activity phenotypes were found in obese mice. Moreover, there were increased DCreg (CD11bhigh DC) cells and decreased CD4+ and CD8+T cells detected in the HFD abortion-prone mice relative to those fed the NCD diet. Our findings reveal how pregnancy obesity and maternal immune regulation are mutually influenced. It is worth noting that the abortion-prone model where active maternal immune status was intensified by obesity, in turn stimulated an overcompensation response, leading to an over-tolerized immune status, and predisposing to potential risks of perinatal complications.